Post-translational modifications and bronchopulmonary dysplasia - Yang, Kun; He, Ting; Sun, Xue; Dong, Wenbin (Frontiers in Pediatrics, 2025)
Bronchopulmonary dysplasia is a prevalent respiratory disorder posing a significant threat to the quality of life in premature infants. Its pathogenesis is intricate, and therapeutic options are limited. Besides genetic coding, protein post-translational modification plays a pivotal role in regulating cellular function, contributing complexity and diversity to substrate proteins and influencing various cellular processes. Substantial evidence indicates that post-translational modifications of several substrate proteins are intricately related to the molecular mechanisms underlying bronchopulmonary dysplasia. These modifications facilitate the progression of bronchopulmonary dysplasia through a cascade of signal transduction events. This review outlines the relationships between substrate protein phosphorylation, acetylation, ubiquitination, SUMOylation, methylation, glycosylation, glycation, S-glutathionylation, S-nitrosylation and bronchopulmonary dysplasia. The aim is to provide novel insights into bronchopulmonary dysplasia's pathogenesis and potential therapeutic targets for clinical management.